Institutional benchmarking of foreign aid effectiveness in Africa - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
This paper integrates two main strands of the aid-development nexus in assessing whether institutional thresholds matter in the effectiveness of foreign aid on institutional development in 53 African countries over the period 1996-2010. Eight government quality indicators are employed: rule of law, regulation quality, government effectiveness, corruption, voice & accountability, control of corruption, political stability and democracy. Three hypotheses are tested and the following findings are established: (1) Institutional benefits of foreign-aid are contingent on existing institutional levels in Africa. (2) But for a thin exception (democracy), foreign-aid is more negatively correlated with countries of higher institutional quality than with those of lower quality. (3) The institutional benefits of foreign-aid are not questionable until greater domestic institutional development has taken place. The reverse is true instead. Government quality benefits of development assistance are questionable in African countries irrespective of prevailing institutional quality levels.
Keywords: B20; F35; F50; O10; O55; 330; Foreign Aid; Political Economy; Development; Africa